The Brain, A Decoded Enigma - Moisa, Dorin Teodor (Salt Lake City, UT : Project Gutenberg, 2005)
"The Brain, A Decoded Enigma" by Dorin Teodor Moisa is a scientific publication written in the early 21st century. The book presents a new theory called Modeling Devices Theory (MDT), which aims to offer a comprehensive understanding of the hardware functions of the brain, both human and animal. It challenges existing paradigms in neuroscience and psychology, proposing a symbolic model for brain function that relies on mathematical logic and precise definitions rather than descriptive terms. At the start of the book, Moisa introduces his original theory, outlining the fundamental concepts and terminology that underpin it. He details how the brain processes information through various models$1 (Bimage and symbolic models$1 (Band discusses their roles in understanding external reality and predicting outcomes through simulations. He emphasizes the need for stability in these models for effective functioning, while also noting the deficiencies inherent in the human design. The opening lays a foundation for exploring complex topics like knowledge, consciousness, and behavioral responses, ultimately setting the stage for a deeper examination of the human brain's capabilities and limitations. (This is an automatically generated summary.)s
Release date is 2005-01-04
Keywords: Brain